Identificação de espécies fúngicas nas onicomicoses do idoso institucionalizado - Vasconcellos, Cidia; Pereira, Carolina Queiroz Moreira; Souza, Marta Cristina; Pelegrini, Andrea; Freitas, Roseli Santos; Takahashi, Juliana Possato [UNESP] (FapUNIFESP (SciELO), 2013)
BACKGROUND: Superficial fungal infections are caused by dermatophytes, yeasts or filamentous fungi. They are correlated to the etiologic agent, the level of integrity of the host immune response, the site of the lesion and also the injured tissue. OBJECTIVE: The purpose of this study is to isolate and to identify onychomycosis agents in institutionalized elderly (60 years old +). METHODS: The identification of the fungi relied upon the com-bined results of mycological examination, culture isolation and micro cultures observation under light microscopy from nail and interdigital scales, which were collected from 35 elderly with a clinical suspicion of onychomycosis and a control group (9 elderly with healthy interdigital space and nails). Both groups were insti-tutionalized in two nursing homes in Sao Bernardo do Campo, SP, Brazil. RESULTS: The nail scrapings showed 51.40% positivity. Of these, dermatophytes were found in 44.40% isolates, 27.78% identified as Trichophyton rubrum and 5.56% each as Trichophyton tonsurans, Trichophyton mentagrophytes and Microsporum gypseum. The second more conspicuous group showed 38.89% yeasts: 16.67% Candida guilliermondii, 11.11% Candida parapsilosis, 5.56% Candida glabrata, and 5.56% Trichosporon asahii. A third group displayed 16.70% filamen-tous fungi, like Fusarium sp, Aspergillus sp and Neoscytalidium sp (5.56% each). The interdigital scrapings pre-sented a positivity rate of 14.29%. The agents were coincident with the fungi that caused the onychomycosis. In the control group, Candida guilliermondii was found at interdigital space in one person. CONCLUSION: Employing a combination of those identification methods, we found no difference between the etiology of the institutional-ized elderly onychomycosis from that reported in the literature for the general population. © 2013 by Anais Brasileiros de Dermatologia.
Identification of fungi species in the onychomycosis of institutionalized elderly
Keywords: Arthrodermataceae; Fungi; Health of institutionalized elderly; Onychomycosis; aged; Arthroderma gypseum; Candida glabrata; Candida parapsilosis; clinical article; controlled study; dermatophyte; female; fungus identification; human; male; microscopy; nail dystrophy; onychomycosis; Pichia guilliermondii; Trichophyton mentagrophytes; Trichophyton rubrum; Trichosporon asahii; yeast